STUDI PEMBUATAN MIE INSTAN DENGAN MENGGUNAKAN BAHAN BAKU JAGUNG KUNING DAN JAGUNG PULUT - Andi Nurfitriani (AkMen JURNAL ILMIAH, 2011)
Corn Instant noodle is one of food diversification. Corn instant noodle in this research used yellow corn and waxy as raw materials. Yellow corn contained high amylose while waxy corn has higher amylopectin the higher the stickiness. This research aims was to know the best process in making instant noodle and to know the best corn flour in making corn instant noodle. Research’s treatments were yellow corn 100%. Yellow corn and waxy corn with comparison 9:1, 8:2, and 7:3. The parameters were rehidration time and sensory test. The best result were then tested: proximate test for water content, ash, fat, protein, and carbohydrate. The result showed that from color and flavor yellow corn were the best. The taste result of yellow corn and waxy corn with comparison 9:1 showed the best. Addition of waxy corn more than 10% will gave bad effect to noodle product. The fastest rehidration time for yellow corn 100% was 3 minutes 27 second, water content 4,07%, ash content 1,24%, fat content 18,22%, protein content 5,33%, and carbohydrate content 70,99%.